Dispelling myths associated with spread spectrum radio technology in the irrigation industry - Palmer, Peter L., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2008)
Each year, the irrigation and drainage industry deploys an increasing number of Spread Spectrum communication solutions. As recently as five years ago, the use of wireless telemetry in irrigation and drainage SCADA systems was almost exclusively in the licensed radio realm. However, the scarcity of available licensed channels as well as its improved technology has made the Spread Spectrum radio an increasingly popular choice. With the install base of Spread Spectrum devices rapidly increasing, there have been a number of urban legends, superstitions and myths that have circulated. With the introduction and advancement of any new technology, misconceptions and misunderstandings will always surface. Spread Spectrum, like any technology, can be an extremely valuable tool when used in the correct environment and with correct network deployment. The objective of this presentation is to explore these "myths" and provide a better understanding of how to use Spread Spectrum technology in irrigation and drainage applications and also show where you can expect to succeed with Spread Spectrum communication solutions.
Urbanization of irrigated land and water transfers
Radio technology
Not digitized by CSUL Digital Services.
Presented at Urbanization of irrigated land and water transfers: a USCID water management conference on May 28-31, 2008 in Scottsdale, Arizona.